(3SDGd cejd ddEeGe Ydi QVi Gddg Yfgs ((3Cejf Hf NjQ Gddg GdYeQi GdNWjH s)
(3ChdgG (B:s
(3bhdg bGd cejd GdYdi QVgeG GdMbjbI Ci Ci TF MbjbI NGdbfG hQGRbfG hGdefYe YdjfG BfGA Gddjd hCWQGa GdfgGQ s
(3BNQgG (B:s
(3hEfg djS ceKdg TF hGfg bOje CRdi HdG EHJOGA agh CHOi hfYe eG bjd ai GdHYQI JOd Ydi GdHYjQ ade de JOd GdSehGJ hGdCQV Ydi GddWja GdNHjQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B12s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs